177Lu-Dotatate plus long-acting octreotide versus high‑dose long-acting octreotide in patients with midgut neuroendocrine tumours (NETTER-1): final overall survival and long-term safety results from an open-label, randomised, controlled, phase 3 trial. Issue 12 (December 2021) - Strosberg, Jonathan R; Caplin, Martyn E; Kunz, Pamela L; Ruszniewski, Philippe B; Bodei, Lisa; Hendifar, Andrew; Mittra, Erik; Wolin, Edward M; Yao, James C; Pavel, Marianne E; Grande, Enrique; Van Cutsem, Eric; et al.
Summary: Background: The primary analysis of the phase 3 NETTER-1 trial showed significant improvement in progression-free survival with 177 Lu-Dotatate plus long-acting octreotide versus high-dose long-acting octreotide alone in patients with advanced midgut neuroendocrine tumours. Here, we report the prespecified final analysis of overall survival and long-term safety results. Methods: This open-label, randomised, phase 3 trial enrolled patients from 41 sites in eight countries across Europe and the USA. Patients were 18 years and older with locally advanced or metastatic, well differentiated, somatostatin receptor-positive midgut neuroendocrine tumours (Karnofsky performance status score ≥60) and disease progression on fixed-dose long-acting octreotide. Patients were randomly assigned (1:1) via an interactive web-based response system to intravenous 177 Lu-Dotatate 7·4 GBq (200 mCi) every 8 weeks (four cycles) plus intramuscular long-acting octreotide 30 mg ( 177 Lu-Dotatate group) or high-dose long-acting octreotide 60 mg every 4 weeks (control group). The primary endpoint of progression-free survival has been previously reported; here, we report the key secondary endpoint of overall survival in the intention-to-treat population. Final overall survival analysis was prespecified to occur either after 158 deaths or 5 years after the last patient was randomised, whichever occurred first. During long-term follow-up, adverse events of special interest were reported in the 177 Lu-Dotatate group only. This trial is registered with ClinicalTrials.gov, NCT01578239 . Findings: From Sept 6, 2012, to Jan 14, 2016, 231 patients were enrolled and randomly assigned for treatment. The prespecified final analysis occurred 5 years after the last patient was randomly assigned (when 142 deaths had occurred); median follow-up was 76·3 months (range 0·4–95·0) in the 177 Lu-Dotatate group and 76·5 months (0·1–92·3) in the control group. The secondary endpoint of overall survival was not met: median overall survival was 48·0 months (95% CI 37·4–55·2) in the 177 Lu-Dotatate group and 36·3 months (25·9–51·7) in the control group (HR 0·84 [95% CI 0·60–1·17]; two-sided p=0·30). During long-term follow-up, treatment-related serious adverse events of grade 3 or worse were recorded in three (3%) of 111 patients in the 177 Lu-Dotatate group, but no new treatment-related serious adverse events were reported after the safety analysis cutoff. Two (2%) of 111 patients given 177 Lu-Dotatate developed myelodysplastic syndrome, one of whom died 33 months after randomisation (this person was the only the only reported 177 Lu-Dotatate treatment-related death). No new cases of myelodysplastic syndrome or acute myeloid leukaemia were reported during long-term follow-up. Interpretation: 177 Lu-Dotatate treatment did not significantly improve median overall survival versus high-dose long-acting octreotide. Despite final overall survival not reaching statistical significance, the 11·7 month difference in median overall survival with 177 Lu-Dotatate treatment versus high-dose long-acting octreotide alone might be considered clinically relevant. No new safety signals were reported during long-term follow-up. Funding: Advanced Accelerator Applications, a Novartis company.